Dampak Fermentasi Kulit Pisang terhadap Peningkatan Produktivitas Tanaman Cabai - Ardina Larasati (SUAN PUBLISHER, 2024)
This study aims to examine the impact of fermented banana peel waste application on increasing the productivity of chili plants (Capsicum spp.). Banana peels, as abundant agricultural waste, are rich in potassium (K), phosphorus (P), and essential micronutrients, making them a potential organic fertilizer. The fermentation process can increase the availability of these nutrients as well as add beneficial decomposing microorganisms to the soil. This study will use a field experiment method with a Randomized Block Design (RAK) involving several concentration levels of fermented banana peel liquid organic fertilizer (POC). The parameters observed include vegetative growth (plant height, number of leaves), generative growth (number of flowers, number of fruits), and harvest yield (fruit weight per plant). Predictive results indicate that the application of fermented banana peel POC at optimal concentrations will significantly increase the growth and productivity of chili plants compared to the control. This study is expected to provide practical recommendations for farmers in utilizing agricultural waste for more sustainable chili cultivation.